Sistem Pendukung Keputusan Penentuan Lokasi Perbaikan Jalan Menggunakan Metode Simple Additive Weighting (SAW) (Studi Kasus : Dinas P.U Bina Marga Kabupaten Ogan Ilir) - Resi resi; Ali Ibrahim (Universitas Sriwijaya, 2020)
Currently the system to determine the location of roadworks at the Department of Public Works Highways Ogan Ilir already running properly with the working guidelines of government regulation No. 34 of 2006 on the road needs to be improved in accordance with the streets according to their status as district roads. However, the process to determine which path should be repaired first they compare with the printed document, so that problems that occur are not effective in the process of decision-making and reporting. Therefore, this study about decision support systems determining the location of roadwork that aims to speed up the decision making process regarding the location of which road to be repaired first by a ratio of specified criteria. The method used mainly in the development of the system is a Simple Additive weighting method (SAW) that can help best decision against several alternative decisions to obtain an accurate and optimal decision. The system is developed using PHP programming language and MySQL database in order to produce a support system that can provide an alternative in the decision.